2016
DOI: 10.1097/j.pain.0000000000000775
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in pain: understanding the mosaic that makes pain personal

Abstract: The experience of pain is characterized by tremendous inter-individual variability. Multiple biological and psychosocial variables contribute to these individual differences in pain, including demographic variables, genetic factors, and psychosocial processes. For example, sex, age and ethnic group differences in the prevalence of chronic pain conditions have been widely reported. Moreover, these demographic factors have been associated with responses to experimentally-induced pain. Similarly, both genetic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
341
1
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 422 publications
(360 citation statements)
references
References 87 publications
(119 reference statements)
6
341
1
12
Order By: Relevance
“…The older hospitalised person with unrelieved pain will have a worsening of their cognitive status, increased depression, more comorbidities and a longer length of stay (Corsi et al, 2018). Fillingim (2017) has noted a gradual increase in the awareness of the effects of under-treatment of pain for the older person; this finding was considered to contribute to greater recognition of pain management in this population group. Additionally, Tavernier et al (2018) identified the organisational context in which nurse-led pain care provision was provided would act as either a barrier or a facilitator in relation to pain care provision.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The older hospitalised person with unrelieved pain will have a worsening of their cognitive status, increased depression, more comorbidities and a longer length of stay (Corsi et al, 2018). Fillingim (2017) has noted a gradual increase in the awareness of the effects of under-treatment of pain for the older person; this finding was considered to contribute to greater recognition of pain management in this population group. Additionally, Tavernier et al (2018) identified the organisational context in which nurse-led pain care provision was provided would act as either a barrier or a facilitator in relation to pain care provision.…”
Section: Introductionmentioning
confidence: 99%
“…(Herr, Coyne, McCaffery, Manworren, & Merkel, 2011). Although self-report is the gold standard, for those unable to communicate, a glimpse may be gained into their experiences by observations of their behaviour (Fillingim, 2017). A person's individual response to pain can be expressed nonverbally as a behaviour such as a change in facial expression or body movement, and this will be influenced by social, cultural and psychological factors .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to education on rest and physical activity, neurophysiological education is very important. is is a cognitive-behavioural intervention to provide knowledge of neurophysiology and neuroscience of pain in order to change beliefs about illness, disability, and above all adaptation to pain [53][54][55]. e management should differentiate the origin of pain, both in terms of mechanical (motor) stimulus and the protective (nociceptive) mechanism [56][57][58][59][60].…”
Section: Introductionmentioning
confidence: 99%
“…I tillegg kan også psykiske og sosiokulturelle forhold forklare kjønnsforskjeller relatert til smerte (6). Jenter og gutter vokser opp med ulike forventninger til smerte: Ofte føler jenter seg mer frie til å gråte om de utsettes for skade, mens gutter gjerne føler et ekstra sosialt press for å holde tilbake tårene.…”
unclassified